Real‐world use of elbasvir‐grazoprevir in patients with chronic hepatitis C: retrospective analyses from the TRIO network. Issue 11 (17th April 2018) - Flamm, S. L.; Bacon, B.; Curry, M. P.; Milligan, S.; Nwankwo, C. U.; Tsai, N.; Younossi, Z.; Afdhal, N.
Summary: Background: Elbasvir‐grazoprevir is indicated for chronic hepatitis C virus (HCV) genotypes 1 and 4. Aim: To evaluate the utilization and outcomes of chronic HCV patients treated with elbasvir‐grazoprevir in the United States. Methods: We conducted a retrospective cohort study of adults treated with elbasvir‐grazoprevir with or without ribavirin for chronic HCV genotypes 1 or 4 infection. Data were collected from healthcare providers and specialty pharmacies through Innervation Platform, a proprietary, cloud‐based disease management program from Trio Health. The primary endpoint was per protocol sustained virological response 12 weeks post‐treatment (SVR12). Results: Among 470 patients treated in 2016, 95% had HCV genotype 1 infection, 80% (373/468) were HCV treatment naïve and 70% (327/468) had non‐cirrhotic disease. Almost 3 quarters (73%) of patients received care in community practices. The majority (89%) of patients received elbasvir‐grazoprevir for 12 weeks. Per protocol SVR12 rates were 99% (396/402) for HCV genotype 1 and 95% (21/22) for HCV genotype 4. Among patients with Stage 4 or 5 chronic kidney diseases, 99% (113/114) achieved SVR12. In univariate analyses, variables significantly associated with per protocol SVR12 for the entire sample were therapy duration ( P = 0.001), treatment experience ( P = 0.016), and cirrhosis status ( P = 0.001). However, among HCV genotype 1 patients, no variables were significant. Intent‐to‐treat SVR12 rates were 89% (396/447) for HCV genotype 1 and 91% (21/23) for HCV genotype 4. Conclusion: Elbasvir‐grazoprevir is highly effective, and in this 2016 cohort, its use was predominantly in patients with HCV genotype 1 and as a 12‐week therapy without ribavirin. Abstract : Linked Content This article is linked to Rumi and Occhipinti and Flamm papers. To view these articles visithttps://doi.org/10.1111/apt.14792 andhttps://doi.org/10.1111/apt.14826 .